Optimisation of extraction and sludge dewatering efficiencies of bio-flocculants extracted from Abelmoschus esculentus (okra) - Lee, Siah Lee; Chong, Mei Fong; Robinson, John P.; Binner, Eleanor (Elsevier, 2015)
The production of natural biopolymers as flocculants for water treatment is highly desirable due to their inherent low toxicity and low environmental footprint. In this study, bio-flocculants were extracted from Hibiscus/Abelmoschus esculentus (okra) by using a water extraction method, and the extract yield and its performance in sludge dewatering were evaluated. Single factor experimental design was employed to obtain the optimum conditions for extraction temperature (25–90 °C), time (0.25–5 h), solvent loading (0.5–5 w/w) and agitation speed (0–225 rpm). Results showed that extraction yield was affected non-linearly by all experimental variables, whilst the sludge dewatering ability was only influenced by the temperature of the extraction process. The optimum extraction conditions were obtained at 70 °C, 2 h, solvent loading of 2.5 w/w and agitation at 200 rpm. Under the optimal conditions, the extract yield was 2.38%, which is comparable to the extraction of other polysaccharides (0.69–3.66%). The bio-flocculants displayed >98% removal of suspended solids and 68% water recovery during sludge dewatering, and were shown to be comparable with commercial polyacrylamide flocculants. This work shows that bio-flocculants could offer a feasible alternative to synthetic flocculants for water treatment and sludge dewatering applications, and can be extracted using only water as a solvent, minimising the environmental footprint of the extraction process.